Exploring AI-Driven Cognitive Conflict in Teaching Quantum Physics : A Case Study in Indonesian Senior High School - Said, Fathiah Damri (Southeast Asian Journal on Open and Distance Learning, 2025)
This study explores the use of generative AI, specifically ChatGPT, as a tool to facilitate cognitive conflict during quantum physics learning in an Indonesian high school classroom. Employing an exploratory case study design, the research involved 200 12th-grade students from a public secondary school. A set of conceptual questions rooted in quantum phenomena (e.g., time travel, superposition) were designed to trigger students’ misconceptions and stimulate metacognitive reflection. Students explored these questions using ChatGPT before engaging in classroom discussion and reflection. While the approach successfully sparked curiosity and deep engagement, analysis revealed that a majority of students relied entirely on AI-generated responses, even for prompts requiring personal opinion. The triangulation analysis combined heuristic linguistic features, response similarity checks, and follow up interview to determine whether student responses were likely generated by AI or written personally and identified key themes of wonder, cognitive ambiguity, and culutural connection in student reflections. Overall, the study highlights both the opportunities and challenges of integrating generative AI into science education.